Molecular Hinges Stabilize Formamidinium‐Based Perovskite Solar Cells with Compressive Strain. (14th April 2022) - Shi, Congbo; Song, Qizhen; Wang, Hao; Ma, Sai; Wang, Chenyue; Zhang, Xiao; Dou, Jie; Song, Tinglu; Chen, Pengwan; Zhou, Huanping; Chen, Yihua; Zhu, Cheng; et al.
Abstract: Formamidinium (FA)‐based lead triiodide have emerged as promising light‐harvesting materials for solar cells due to their intriguing optoelectronic properties. However, obstacles to commercialization remain regarding the primary intrinsic materials instability, wherein volatile organic components of FA + cations are prone to escape under operational stressors. Herein, stabilizing FA‐based perovskite through toughening the interface with the symmetric molecule of 1, 1′‐(Methylenedi‐4, 1‐phenylene) bismaleimide (BMI) is reported. BMI with two maleimides can simultaneously bind with FA + and/or undercoordinated Pb 2+ through chemical bonding, which also compresses the resultant perovskite lattice. The chemical bonding and strain modulation synergistically not only passivate film defects, but also inhibit perovskite decomposition, thus significantly improving the intrinsic stability of perovskite films. As a result, the BMI‐modified perovskite solar cells (PSCs) show improved power conversion efficiency (PCE) from 21.4% to 22.7% and enhanced long‐term operational stability, maintaining 91.8% of the initial efficiency after 1000 h under continuous maximum power point tracking. The findings shed light on the synergetic effects of chemical interactions and physical regulations, which opens a new avenue for stable and efficient perovskite‐based optoelectronic devices. Abstract : In this study, how chemical interaction modulates crystal strain from the molecular perspective is presented, and the size matching between molecular configuration and lattice constant is proposed. The combination of chemical bonding and physically compressive strain stabilizes the perovskite lattice, and the devices exhibit excellent optoelectronic properties and stability. This study opens a new avenue for stable and efficient perovskite‐based optoelectronic devices.